2019
DOI: 10.1049/iet-ipr.2018.6697
|View full text |Cite
|
Sign up to set email alerts
|

Blind text images deblurring based on a generative adversarial network

Abstract: Recently, text images deblurring has achieved advanced development. Unlike previous methods based on hand‐crafted priors or assume specific kernel, the authors recognise the text deblurring problem as a semantic generation task, which can be achieved by a generative adversarial network. The structure is an essential property of text images; thus, they propose a structural loss function and a detailed loss function to regularise the recovery of text images. Furthermore, they learn from the coarse‐to‐fine strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…Qing Qi et al achieved blind text images deblurring based on a generative adversarial network. The experimental results showed that the proposed network was comparable to the state‐of‐the‐art methods [30]. These are image deblurring methods based on the traditional image sensors.…”
Section: Introductionmentioning
confidence: 79%
“…Qing Qi et al achieved blind text images deblurring based on a generative adversarial network. The experimental results showed that the proposed network was comparable to the state‐of‐the‐art methods [30]. These are image deblurring methods based on the traditional image sensors.…”
Section: Introductionmentioning
confidence: 79%
“…By controlling the angles ∠(w r ∇v r , ∇v m D ) and ∠(w f ∇v f , ∇v m D ) to be acute (see Figure 2) when one of them becomes obtuse, one can prevent the issue that training may benefit one loss but significantly harm the other. However, in previous models [4][5][6][7][8][9][30][31][32][33][34], the loss function of the discriminator consists of two equally weighted parts, that is,…”
Section: Robustness Analysismentioning
confidence: 99%
“…Since the introduction of GANs, many variants have been proposed [2][3][4][5] to improve the generated image quality. Although GANs have already been successfully used in image generation and image editing [6][7][8][9], they are notoriously difficult to train, and it has been observed that they often suffer from mode collapse [10,11], which causes the generator network to produce results with poor generalizability; that is, a limited variety of samples are produced, but many other modes are missed.…”
Section: Introductionmentioning
confidence: 99%